Determination of optimal reaction temperature and hydrogen amount for propylene polymerization by a mathematical model - Varshouee, Gholam Hossain; Heydarinasab, Amir; Vaziri, Ali; Zarand, Seyed Mehdi Ghafelebashi (2019)
Regarding the complexity of Ziegler-Natta catalyst kinetics in polypropylene polymerization, so far, there is no adequate model to determine the best process conditions for predicting average molecular weight and dispersity as the most crucial final product properties index. Consequently, a validated model has been developed which describes the relationship between the kinetic model and the existing gap using the polymer moment balance approach. It was concluded that increasing reaction temperature and hydrogen amount are useful and improve the final product indices to a certain limit, but afterwards they have harmful effects on the indices.
S obzirom na kinetičku složenost Ziegler-Natta katalizatora u polipropilenskoj polimerizaciji, za sada ne postoji odgovarajući model za određivanje optimalnih uvjeta procesa za predviđanje prosječne molekularne mase i disperzije kao najvažnijih indeksa svojstava konačnog proizvoda. Slijedom toga, razvijen je validirani model koji opisuje odnos između kinetičkog modela i postojećeg jaza pristupom ravnoteže momenata. Zaključeno je da su povišena temperatura reakcije i količina vodika korisni i do određene granice poboljšavaju indekse gotovog proizvoda, ali nakon toga na indekse imaju štetni učinak.
Bibliografija: 14 jed.
Summary ; Sažetak.
Keywords: Propilen -- Polimerizacija propilena -- Temperatura reakcije -- Molekularna masa -- Disperzija -- Optimizacija -- Matematičko modeliranje